Bridging Musical Worlds. Arrangements of Works by Debussy in the Repertoire of the Sousa Band - Fasshauer, Tobias (Revue musicale OICRM)

(untitled) (OICRM, 2014)
As is generally known, Claude Debussy’s cakewalks and cakewalk-inflected compositions are a response to the ragtime craze that was stimulated in Paris by the performances of the American “March King” John Philip Sousa and his band in 1900 and 1903. Far less familiar is the fact that the Sousa Band in turn played a handful of transcriptions of works by Debussy in later years. Considering the instrumentation and the popular character of Sousa’s ensemble, his embracing of Debussy may seem surprising at first sight. However, a well-balanced mixture of ‘vernacular’ and ‘cultivated’ music and the employment of the latter for the sake of entertainment was the hallmark of his style of programming. Still it can be said that the Debussy arrangements, along with transcriptions of certain works by Richard Strauss, represent the highest degree of sophistication and modernity that could ever be found in Sousa Band programmes. Focusing on the analysis of transcriptions of the Prélude à l’après-midi d’un faune by Sousa and of La cathédrale engloutie by Herbert L. Clarke (both written in 1921), this article aims to demonstrate that the departure from musical conventions in Debussy’s works required a fresh approach to band scoring which could only partially build on contemporary standards. Thus, arranging Debussy for wind band did not only mean crossing borders in a social and aesthetic sense but also in a technical one. Since traces of impressionist compositional thinking can even be found at some points in Sousa’s own works, the American bandmaster may be regarded as a pioneer of the popular adaptation of impressionist elements that soon would be common in the music of Broadway, Tin Pan Alley and Hollywood.